(untitled) (Research, Society and Development, 2021)
This study aimed to assess the understanding of the educational booklet in a comic book format with educators. The methodology used in the field research was descriptive, with a qualitative approach, 64 teachers participated in the study, data collection took place through the WhatsApp and Messenger applications with the sending of the educational booklet in Portable Document Format – PDF and the questionnaire with 13 questions with subsequent discursive analysis. The data served as support for the elaboration of an educational booklet on Attention Deficit Hyperactivity Disorder, which contains theoretical material to be used by educators with children who have this disorder. The results obtained reinforced the importance of understanding aspects of the behavior of students with ADHD, through the understanding of the disorder. It is believed that the educational booklet can contribute to the knowledge of educators about Attention Deficit Hyperactivity Disorder, providing them with subsidies to deal with students with the disorder.